COPD Trend in Slum Population of Dhaka City and Social Awareness to Combat Its Effect (Delta Medical College Journal, 2025)
Background: A major cause of illness worldwide is chronic respiratory disorders. There is a strong upward trend towards the global incidence of these diseases. An additional 500 million people are affected by it. Objective: The research aimed to quantify chronic obstructive pulmonary disease (COPD) incidence in the slum of Dhaka City. Materials and method: A population-based survey was conducted using a well designed questionnaire. The research included all persons older than 20 years who live and intend to engage in the analysis in the identified slums in Dhaka City. Total 584 samples were calculated using a minimum prevalence of 4.7% at 95% confidence intervals with an allowable error of 20%. Results: The prevalence of COPD was found to be 3.25%. This study also found that there were high rates of illiteracy and low levels of education which tended to accompany limited awareness of COPD and hygiene. Therefore, slum dwellers in Dhaka city live with high health risks and at the same time they have limited knowledge about how to alleviate these risks. Conclusion: Slum population in Dhaka city is expected to continue to have COPD-related respiratory symptoms. When health problems arise, they have limited knowledge about first aid, what treatments and services are available, and where they are available.Delta Med Col J. Jan 2022;10(1): 14-19